(untitled) (Swiss Medical Weekly, 2019)
AIM OF STUDY To report our experience of late correction after infancy in patients with tetralogy of Fallot (ToF). METHODS Observational single-centre retrospective analysis of the surgical techniques and perioperative development of patients from developing countries undergoing total surgical correction of ToF after infancy, between 1 November 2011 and 30 November 2016. Variables are presented as numbers with percentages or as mean ± standard deviation. Due to the setting of the humanitarian programme, clinical and echocardiographic follow-up procedures could be conducted for only one month postoperatively. RESULTS Twenty-five children (mean age: 70.8 ± 42 months, range 23-163; 44% female) underwent total surgical correction of ToF. Two patients (0.8%) initially received a Blalock-Taussig shunt and underwent subsequent correction 24 and 108 months later, respectively. Preoperative mean right ventricular/pulmonary artery (RV/PA) gradient was 84 ± 32 mm Hg, with a Nakata index of 164 ± 71 mm2/m2. Major aortopulmonary collateral arteries (MAPCAs) were observed in eight children (32%), six (26%) of whom underwent transcatheter closure before surgery. 24 children (96%) underwent a valve-sparing pulmonary valve repair and one patient received a transannular patch (TAP). There were no cases which saw major adverse cardiac and cerebrovascular events (MACCE). Mean duration of mechanical ventilation was 28 ± 19.6 hours (range 7-76). Pre-discharge echocardiography demonstrated a mean RV/PA gradient of 25 ± 5.7 mm Hg, with left ventricular ejection fraction >60% in all cases. Overall length of hospital stay was 11.7 ± 4.5 days. There were no in-hospital mortality cases. CONCLUSIONS Late surgical correction of ToF can be safely performed and produce highly satisfying early postoperative results comparable to those of classical “timely” correction. A valve-sparing technique can be applied in the majority of children.